2021
DOI: 10.1186/s13049-021-00929-8
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of helicopter emergency medical services in the pre-hospital care of penetrating torso injuries in a semi-rural setting

Abstract: Background Although the merit of pre-hospital critical care teams such as Helicopter Emergency Medical Services (HEMS) has been universally recognized for patients with penetrating torso injuries who present with unstable physiology, the potential merit in patients initially presenting with stable physiology is largely undetermined. The ability to predict the required pre-hospital interventions patients may have important implications for HEMS tasking, especially when transport times to definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Gender and Age: Young males are most likely to be victim of violent crimes involving knives according to the majority of published data [15][16][17][18][19][20][21][22][23][24][25][26][27]. A 2017 systematic review by Whittaker et Al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender and Age: Young males are most likely to be victim of violent crimes involving knives according to the majority of published data [15][16][17][18][19][20][21][22][23][24][25][26][27]. A 2017 systematic review by Whittaker et Al.…”
Section: Discussionmentioning
confidence: 99%
“…Gavrilovski et Al. [27] have demonstrated that violence involving knives is increasing outside of urban centres and may be linked to the creation of so called "county lines" [28]. This implicates that SPT is frequently drug related, either through distribution or consumption.…”
Section: Data Sourcementioning
confidence: 99%
“…The decision to initiate transfusion in a patient with suspected haemorrhagic shock is both complex and time-critical and is based on a variety of symptoms, clinical presentations and mechanisms of injury. In patients presenting with unstable physiology or clinical signs on scene, a certain degree of overtransfusion may be inevitable [27]. Although increased survival to hospital in trauma patients receiving out of hospital transfusion of PRBC has been shown, this does not necessarily translate into increased long-term survival [28].…”
Section: Discussionmentioning
confidence: 99%